(untitled) (Indian Journal of Public Health Research & Development, 2025)
Health massage industry was adversely affected by COVID-19 crisis. Owner and operators changed their business procedures into new normal operations by adapting protective measures and practices in their venues. Thus, this study purposed to examine influencing factors towards COVID-19 preventive practices of health massage entrepreneurs in Phetchabun Province for establishment development and to evaluate relationships among knowledge, attitude, and practice. This cross-sectional survey was carried out from January – March, 2022 involving 76 health massage entrepreneurs registered and reopened business in early 2022. The participants were recruited by purposive sampling technique. Data was collected through a self-administrated questionnaire and a “Self-Assessment for Health Establishments to Prevent and Control Coronavirus Disease 2019 (COVID-19)”. Descriptive statistics, one-way analysis of variance (ANOVA), and Pearson correlation coefficient were applied to analyze data. Findings revealed different educational attainments and monthly incomes had significant relationships with COVID-19 preventive practices. The analysis showed the entrepreneurs held diploma / higher vocational certificate and earned monthly incomes 186-258 USD highly demonstrated protective practices. There were found positive correlation of knowledge and practice (r=0.310, p=0.006) and between attitude and practice (r=0.313, p=0.006). Education on COVID-19 preventive behaviors was suggested to promote via credible multiple platforms and subsequently encourage optimistic attitude and motivate favorable practices.